2015
DOI: 10.3892/or.2015.4015
|View full text |Cite
|
Sign up to set email alerts
|

Reduced expression of semaphorin 4D and plexin-B in breast cancer is associated with poorer prognosis and the potential linkage with oestrogen receptor

Abstract: Abstract. Involvement of semaphorin 4D (Sema4D) and the receptor proteins of the plexins B family (plexin-B1, -B2 and -B3) in solid tumours suggests they play a role in breast cancer. In the present study, the expression of Sema4D and plexin-Bs was examined in a breast cancer cohort. The expression of Sema4D and plexin-Bs was examined in 147 tumours together with 22 normal mammary tissues using quantitative PCR along with clinicopathological patient data, as well as in MCF-7 and MDA-MB-231 cell lines treated w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
33
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(34 citation statements)
references
References 41 publications
1
33
0
Order By: Relevance
“…It is plausible that plexin-B2 brings Rnd3 and p190RhoGAP together to enhance Rnd3-induced rounding. The role of plexin-B2 as a target for Rnd3 signalling could explain the apparently opposing effects of plexin-B2 in cancer cell invasion and cancer progression: in some cancer types such as breast cancer, both Rnd3 and plexin-B2 appear to inhibit hallmarks of tumorigenesis (Malik et al, 2015; Zhu et al, 2014), whereas in gliomas they promote tumour progression (Clarke et al, 2015; Le et al, 2015). …”
Section: Discussionmentioning
confidence: 99%
“…It is plausible that plexin-B2 brings Rnd3 and p190RhoGAP together to enhance Rnd3-induced rounding. The role of plexin-B2 as a target for Rnd3 signalling could explain the apparently opposing effects of plexin-B2 in cancer cell invasion and cancer progression: in some cancer types such as breast cancer, both Rnd3 and plexin-B2 appear to inhibit hallmarks of tumorigenesis (Malik et al, 2015; Zhu et al, 2014), whereas in gliomas they promote tumour progression (Clarke et al, 2015; Le et al, 2015). …”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, it was reported that the decreased expression of Sema4D and PlexinB1 was associated with local recurrence and poor prognosis in breast cancer [ 10 ]. Although, the expression of Sema4D and PlexinB1 have been investigated in some solid malignancies, the correlation between the expression of these factors and the prognosis of patients with malignant tumors remains controversial.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, the role of Sema4D, via interaction with PlexinB1, in activities such as tumor angiogenesis and invasive growth have been discussed in relation to various types of tumors [ 8 10 ]. Thus, in the present study we investigated the expression of Sema4D and PlexinB1 in CRC tissue specimens and assessed their association with various clinicopathological factors.…”
Section: Introductionmentioning
confidence: 99%
“…Extraction of RNA and synthesis of cDNA. RNA was isolated from both tumor and control tissues using TRIzol ® (Invitrogen, Carlsbad, CA, USA) as mentioned earlier (9). After extraction, RNA was dissolved in diethyl pyrocarbonate (DEPC)-treated autoclaved water and stored at −80˚C until further use.…”
Section: Methodsmentioning
confidence: 99%